CO2 electrolysis in a reversible molten carbonate fuel cell: Online chromatographic detection of CO. (21st April 2021) - Meskine, H.; Gürbüz, E.; Albin, V.; Meléndez-Ceballos, A.; Cassir, M.; Ringuedé, A.; Lair, V.
Abstract: CO2 plays a major role in the molten carbonate fuel cell (MCFC) and its reverse process, the molten carbonate electrolysis cell (MCEC), because of the capability of the mentioned electrolyte to capture big amounts of this greenhouse gas. In particular, the co-electrolysis process together with water, would ideally yield syngas (H2 + CO). The reduction of CO2 in such a case has been scarcely investigated in MCEC conditions. The present study is mainly focused on the online detection by Gas Chromatography (GC) of CO2 electrolysis product. Both thermodynamic predictions, including the chemical reactivity of CO and CH4, and experimental results on MCFC/MCEC performance and GC detection, allowed to prove that CO is produced electrochemically with a ratio depending on the electrolysis potential, deducing also the potentials that should be avoided to inhibit the formation of carbon. This first insight will be essential for analyzing the medium and long-term performance of MCECs. Highlights: Electrochemical reduction of CO2 into CO was evidenced in molten carbonates. On line gas chromatography allows to quantify CO production. The fuel/electrolysis molten carbonates cell is reversible.